Vietnam Student Discusses First Month Impression - Spartan Daily:::::::::
On March 1, 1967, fifteen students from Vietnam moved to the San Jose State College residence halls for an education program sponsored by the Agency for International Development education program. SJSC was one of seven colleges to participate in the program. (Spartan Daily, March 4, 1967)